Benchmarking the post-accreditation patient safety culture at King Abdulaziz University Hospital - Al-Awa, Bahjat (Ann Saudi Med, 2012)
BACKGROUND AND OBJECTIVES: Accreditation is an internationally recognized evaluation process used to assess, promote, and guarantee efficient and effective patient care and safety. Saudi Arabia is one of the first countries in the eastern Mediterranean region to implement health care accreditation standards. This study provides valuable information pertaining to the impact of accreditation in the unique multicultural, multilingual competitive environment at King Abdulaziz University Hospital in Saudi Arabia. The objective of this study was to perform an unbiased assessment of the impact of accreditation on patient safety culture. DESIGN AND SETTING: Cross-sectional retrospective and prospective study post-accreditation at King Abdulaziz University Hospital in Jeddah, Saudi Arabia from January 1, 2006 to December 31, 2009. PATIENTS AND METHODS: A total of 870 registered nurses from eight different cultural backgrounds working at 22 hospital units were given electronic access to the survey. A 5-point Likert scale was used, ranging from 1 for “Strongly disagree” to 5 for “Strongly agree.” The survey results were matched with the international benchmarks from the Hospital Survey on Patient Safety Culture, 2005. RESULTS: A total of 605 nurses answered the survey questionnaire. The comparison between the percentages of nurses at King Abdulaziz University Hospital (KAUH) and those at international hospitals who answered “Agree” and “Strongly agree” showed a post-accreditation improved perception of the culture of patient safety. CONCLUSIONS: Accreditation has an overall statistically significant improvement in the perception of the culture of patient safety.